Pengaruh Pendidikan Kewirausahaan dan Motivasi Terhadap Minat Berwirausaha Pada Mahasiswa - Atik Lusia; Tri Ratna Pamikatsih (JEBDEKER: Jurnal Ekonomi, Manajemen, Akuntansi, Bisnis Digital, Ekonomi Kreatif, Entrepreneur, 2021)
Entrepreneurship education can be the basis for students to be able to develop their abilities in entrepreneurship. This study aims to determine the effect of entrepreneurship education and entrepreneurial motivation on entrepreneurship intention. This research was conducted on 110 respondents by distributing questionnaires with purposive sampling method and the sampling criteria used were management university students who had taken entrepreneurship education courses. This study applies a descriptive correlational method which is intended to determine the causal relationship of an event. Researchers used a Likert scale for measuring questionnaires and analysis tools using multiple regression. Based on the research, it was found that entrepreneurship education and motivation influence university students in entrepreneurship intention but entrepreneurial motivation has a lower regression value so it is necessary to create activities that can increase students' entrepreneurial motivation.